On the Effectiveness of Active Aeroelastic Structures for Morphing Aircraft - Saavedra-Flores, E (Royal Aeronautical Society, 2013)
This note assesses the benefits of active aeroelastic structures (AAS) in enhancing flight performance and control authority. A representative AAS concept, whose torsional stiffness and shear centre position can be altered depending on the instantaneous flight condition, is employed in the wing of a medium altitude long endurance (MALE) UAV. A multidisciplinary design optimisation (MDO) suite is used in this study. It turns out that AAS can be very effective when used for enhancing control authority of the vehicle but have limited benefits in terms of flight performance (lift to drag).